Centro interpretativo digital do patrimônio cultural município de Dona Francisca - RS - Bortolin, Ana Carolina Cherobini (2022)
Cultural heritage are elements bequeathed by our ancestors that represent a social group, refer to memory, contribute to the formation of identities and to strengthen the bonds of individuals with the place where they live. They are elements that act as a symbolic reference of a community, represent the history and past of a people and are endowed with the meaning of a community life, making it unique. The preservation and appreciation of cultural heritage are important so that the memories, history and past of a people are maintained over time. However, this will only occur if there are affective ties and bonds between the individual and the elements around him, helping them to identify and feel that they belong to a particular culture and/or territory. Identity formation takes place in the social sphere and, as it is a conscious process, it must be evoked or rescued through different actions. The connection between individuals and the construction of identity often occurs through the sharing of symbologies and the search for a common past. In this way, cultural heritage plays an important role in the process of identifying and valuing the elements present in the social environment. Based on this, seeking the preservation and dissemination of the memories and meanings of the representative cultural heritage of the municipality of Dona Francisca, this dissertation aimed to develop a Digital Interpretive Center (CID) of the Cultural Heritage of Dona Francisca, located in the Quarta Colônia do Rio Grande do Sul. The CID is available on a website, presenting the main cultural heritages that are representative for the municipality, allowing the public to interpret and understand the importance and meanings of local heritage. With the elaboration of this product, it is intended to strengthen the affective bonds and the identification of the community with the culture and the territory to which they belong, creating a feeling of pride on the part of individuals, as well as serving as an attraction for the external public to be interested in visit the municipality and discover its cultural legacies.